Coaching researched : a coaching psychology reader - Passmore, Jonathan; Tee, David (Hoboken, NJ : Wiley, 2019)
"This book will be a collection of papers from the BPS publication: International Coaching Psychology Review. The new work would bring together the best papers from the last 15 years of the peer review publication, with the aim of more widely showcasing this research, making more accessible to the growing number of coaching researchers in business, health and education, and practitioners where there is a growing interest in evidenced based practice. The last five years have seen a growth in the number of University courses in the UK, and wider English speaking world; Australia, South Africa, and US, as well as in Europe and beyond. We now estimate some fifty plus universities are offering coaching programmes at post-graduate level, with several hundred under-graduate and post-graduate coaching modules leading to a significant growth in coaching related research activity within universities. A second audience we see for the title are practitioners interested in evidenced based practice. In the early development of coaching the focus was on models, specifically those claiming high impact of magical transformations. The growing rofessionalism of coaching, and the focus of coaching professional bodes such as the International Coach Federation (ICF), Association for Coaching (AC) and European Mentoring and Coaching Council (EMCC) on evidenced based practice, as seen a growth interest in the science of coaching. ICPR's growth has been limited as access to the journal is constrained by the BPS. A paper copy of the journal is published, but due to BPS's approach to its in-house journals' the use of discoverability on the journals is severely constrained. As a result many of the papers are not in wider circulation, among coaching students and coaching academics"--
Includes index.
Description based upon online resource; title from PDF title page (viewed May 4, 2021).
John Wiley and Sons
Keywords: Personal coaching; Positive psychology; Executive coaching; Accompagnement (Psychologie); Psychologie positive; Accompagnement de gestionnaires; Executive coaching; Personal coaching; Positive psychology